The role of sentinel lymph nodes in breast cancer - Nikitenko, R.; Kosovan, V.; Vorotyntseva, K.; Koichev, E. (Journal of Education, Health and Sport, 2022)
Introduction. The problem of improving early diagnosis and prognosis of breast cancer remains one of the most actual for current oncological practice. Taking into account a close correlation between the general prevalence of breast neoplasms and mortality from breast cancer, this problem is not only of professional interest, but also has medical-social and socio-economic significance. The purpose of the study is to improve the quality of the sentinel lymph node detection in patients with breast cancer using ICG. Material and methods. At the period 2009–2016, 400 patients with T1-T3N0M0 breast cancer were operated on. All the patients were divided into two groups using two dyes – Patent Blue and ICG. The patients after mastectomy with a sentinel lymph node biopsy had a clinical diagnosis of T2-T3N0M0 breast cancer more often. In group I, 100 patients had the sentinel lymph node biopsy. Lymph node staining was performed using Patent Blue dye. In group II, sentinel lymph nodes biopsy was conducted with the Patent Blue dye and another fluorescent dye — ICG, which was also injected on the affected side of the breast. After ICG dye introduction, in 15 minutes the stained green lymph nodes were detected using special equipment. Criteria for inclusion of patients in the clinical trial: 1) breast cancer patients of any age with T1-3N0M0, I-II AB disease stage; 2) patients with clinically unaffected lymph nodes N0 after examination. Criteria for exclusion of patients from the clinical trial: The exceptions were T3-T4 tumors > 5 cm in diameter, or the skin and chest wall invasion, as well as palpable axillary lymph nodes, 3 or more affected lymph nodes with sentinel lymph node biopsy; 3) patients after radiation therapy. Results. The tumor histology was performed after the node trephine biopsy. The main aims of sentinel nodes detection were staging and improving the breast cancer patients’ life quality after surgical treatment. The post-mastectomy syndrome, the main manifestation of which is swelling of the upper extremity is a big problem for patients because it affects their life quality and disturbs their usual lifestyle. The sentinel lymph node detection, in contrast to axillary lymph node dissection of I-II level, significantly minimizes all the risks of postmastectomy syndrome, in particular, impaired lymphatic drainage in the form of lymphatic edema of the upper extremity, impaired venous outflow in the form of stenoses or the axillary and/or subclavian veins occlusion, rough scars which limit the function of the extremity in the shoulder joint, and brachioplexitis. Conclusions. The study of sentinel lymph nodes significantly improves the results of surgical treatment of breast cancer patients. Based on the clinical-laboratory and histological examinations, new data were obtained concerning the sentinel lymph node detection using two dyes, the choice of the surgical intervention volume and reduction of complications rate at the postoperative period. We found that fluorescent lymphography is highly effective, which allows to recommend it for implementation into the clinical practice. The frequency of sentinel lymph node detection in breast cancer patients is 98% in the control group, 100% – in the main group. On the basis of the obtained results, the sentinel lymph node detection algorithm and the surgical management of patients with breast cancer was developed and implemented into practice, which allowed to reduce the number of complications with using two dyes for the sentinel lymph node detection from 19% to 2% (χ2 =15.37, p<0.001). Recurrence of breast cancer fell from 13% to 8%.